Selection of a smart and secure education school system based on the internet of things using entropy and TOPSIS approaches - Habib Ullah Khan (12024579) (2024)
Context The Internet of Things (IoT) is playing an important role in the development of cars, smart homes and schools. Schools are using IoT technology to enhance student learning, digitize traditional learning and improve academic performance. IoT is rapidly replacing the traditional school system with a modern, smart and safe school system. Several modern education systems are presented in the literature. Problem statement The difficulty of choosing a smart and safe school system while evaluating the respective merits of different school systems has long been a concern for educators. Method In this study we proposed a hybrid multi-criteria decision-making method (MCDM) to address the selection Problem. To rank the different smart school systems and evaluate the value of the required parameter, two MCDM-based methods are used: Entropy and TOPSIS (Technique for Preference Ordering by Similarity to an Ideal Solution). Results Twelve beneficial features were considered that represent the fundamental positive characteristics required to create an intelligent education system. Ten different educational systems are considered as alternatives in order to carry out an evaluation. Entropy is used to measure the importance of each criterion and TOPSIS is used to rank the school systems. In this paper, we propose how the concepts of Entropy and TOPSIS can be used to address the challenge of selecting a safe and smart school system based on IoT. Our investigation selected the IoT-based school system that was found to be the smartest and safest out of a set of schools. Finally, we discuss the evaluation of the proposed research. Other Information Published in: Computers in Human Behavior License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.chb.2024.108346